Multilingual speech processing - Schultz, Tanja 1964-; Kirchhoff, Katrin (Academic Press, 2006)
Annotation Tanja Schultz and Katrin Kirchhoff have compiled a comprehensive overview of speech processing from a multilingual perspective. By taking this all-inclusive approach to speech processing, the editors have included theories, algorithms, and techniques that are required to support spoken input and output in a large variety of languages. This book presents a comprehensive introduction to research problems and solutions, both from a theoretical as well as a practical perspective, and highlights technology that incorporates the increasing necessity for multilingual applications in our global community. Current challenges of speech processing and the feasibility of sharing data and system components across different languages guide contributors in their discussions of trends, prognoses and open research issues. This includes automatic speech recognition and speech synthesis, but also speech-to-speech translation, dialog systems, automatic language identification, and handling non-native speech. The book is complemented by an overview of multilingual resources, important research trends, and actual speech processing systems that are being deployed in multilingual human-human and human-machine interfaces. Researchers and developers in industry and academia with different backgrounds but a common interest in multilingual speech processing will find an excellent overview of research problems and solutions detailed from theoretical and practical perspectives.* State-of-the-art research with a global perspective by authors from the USA, Asia, Europe, and South Africa* The only comprehensive introduction to multilingual speech processing currently available* Detailed presentation of technological advances integral to security, financial, cellular and commercial applications.
Includes bibliographical references (pages 449-490) and index. - Cover title
Keywords: Speech processing systems; Traitement automatique de la parole